Influence of processing parameters in the mechanical properties enhancement of forsterite ceramic / Tan Yoke Meng - Tan, Yoke Meng (2016)
Phase pure forsterite was synthesized by mechanochemical method owing to its simplicity and low cost process. Different milling methods, i.e. ball milling and attrition milling, were investigated over sintering temperature ranging from 1200 oC to 1500 oC. Upon comparison and selection for the best method based on relative density, Vickers hardness and fracture toughness, the effect of ZnO addition ranging from 0.1-3.0 wt% on the sinterability of forsterite when sintered at 1200 oC to 1500 oC was evaluated. Subsequently, microwave sintering was conducted on both undoped and doped forsterite bulk at temperature ranging from 1100 oC to 1250 oC. In the present study, phase pure forsterite was successfully synthesized upon sintering at 1200 oC and 1300 oC for attrition-milled and ball-milled samples, respectively. It was revealed that attrition milling provides higher grinding energy and particle refinement on the mixtures thus producing powder with significantly smaller particle size as compared to ball-milled powder. The optimum sintering temperature obtained was 1400 oC for both samples having the highest fracture toughness value of 4.3 MPa m1/2 and 3.52 MPa m1/2 for attritor-milled and ball-milled samples, respectively. No decomposition of forsterite was observed throughout the sintering regime. This study had also revealed that the incorporation of 1.0 wt% ZnO into forsterite had enhanced the overall mechanical properties of forsterite with a maximum of 4.51 MPa m1/2 fracture toughness value obtained upon sintering at 1400 oC. In general, all doped samples showed better mechanical properties than the undoped sample at all sintering temperatures studied. In addition, microwave sintering was proven to be beneficial towards the mechanical properties enhancement at a lower sintering temperature with very short sintering duration. Fracture toughness of 4.25 MPa m1/2 was successfully obtained at sintering temperature of 1250 oC for 1.0 wt% ZnO doped sample. The fracture toughness value obtained was 36% higher as compared to the conventional sintered sample under equal sintering temperature. This promising result had shown the potential of microwave sintering in further enhancing forsterite ceramic without sacrificing the phase stability of the material. This research had highlighted the advantageous of using attrition milling in synthesizing phase pure forsterite, the economical production of ZnO doped forsterite having enhanced mechanical properties and the significant reduction in sintering process with acceptable mechanical properties for clinical application via microwave sintering.